Processing of high-performance fluoropolymers by additive manufacturing - Campanelli, Carlo (2019)
Polymers are used in different additive manufacturing (AM) techniques such as material jetting, material extrusion, binder jetting, vat photopolymerisation, sheet lamination, and powder bed fusion. Each technique has slightly different pros and cons but, in general, they are all suited for low-volume production, prototyping, complex geometry, bespoke parts, avoiding the losses of expensive materials (usually involved in traditional fabrication), rapid tooling/mould manufacture, and reverse engineering. Only a small percentage of the available polymers on the market are suitable to be processed with AM techniques as particular material properties are required. The lack of a diversified portfolio of materials is one of the main limitations of AM, thus research in this field is essential for the advancement of the technology and to reduce the gap between AM and the traditional manufacturing industry. This PhD investigated the use of fluoropolymers in AM and identified powder bed fusion and material jetting as the most promising technologies to process these materials. Fluoropolymers represent a particularly interesting family of polymers. PTFE, better known by the trademark Teflon, is the most famous and used fluoropolymer. Because of the particular characteristics of the C-F bond, fluoropolymers have many desirable properties such as biocompatibility, non-adhesiveness, wide service temperature (−260 °C - +260 °C), high chemical resistance, low dielectric constant (insulating), low refractive index, good transparency to UV, visible, and IR light, and high resistance to sunlight, flames, and weathering without the addition of fillers, plasticisers or stabilisers. These properties can be found in other materials but fluoropolymers are unique when two or more of these properties are required in the same application. The downside of all these amazing properties is that fluoropolymers are difficult to process. For example, because of its high crystallinity and viscosity (1010-1012 Pa.s), PTFE is not melt processable like most thermoplastics polymers and requires special processes. The high chemical resistance makes them insoluble in most organic solvents at room temperature. The high temperatures required to process them cause a degradation of the polymer chain which generate corrosive by-products that require specific alloys to be used. The number of challenges further increases in AM as commercially available grades are tailored for more traditional processes such as injection moulding (pellets) and coating (fine powders). The investigation of fluoropolymers in AM is still very limited and mainly focused on one particular fluoropolymer, polyvinylidene fluoride (PVDF) and its copolymers, which has a relative low melting temperature (<180 °C) and piezoelectric properties. This PhD investigates three fluoropolymers: a terpolymer of tetrafluoroethylene, hexafluoropropylene and vinylidene fluoride (THV), polychlorotrifluoroethylene (PCTFE), and perfluoroalkoxy (PFA) with melting temperatures of 110 °C, 210 °C, and 304 °C, respectively. PCTFE and PFA were used in polymer powder bed fusion applications while THV was used in material jetting. Several issues were faced and solved. The first challenge encountered was to find these fluoropolymers in a powder form with an ideal particle size distribution. This was not possible and particle sizes below the optimal values were used. Because of that, the powders were cohesive and did no flow well. Good flowability was achieved by testing several thermal treatments and additives such as fumed nano-silica and carbon black. The second issue was the high melting temperature of PCTFE and PFA which were too high for the powder bed fusion equipment used (EOS Formiga P100, maximum powder bed temperature of 182 °C). The isothermal crystallisation data of PCTFE and PFA confirmed that the ideal processing temperature was above 182 °C for both polymers. This led to a negative and a positive effect. The negative effect was a part warping after few tens of layers for PCTFE and part warping at the first layer for PFA. The positive effect was that the polymers did not age at the processing temperature and could be recycled without issues. Different scan strategies and the use of a build plate reduced considerably the warping. The third issue was the high molecular weight and consequent viscosity of the polymer melt. The melting and solidification of the polymers happened too quickly and the formed layers were porous. Higher laser powers reduced the porosity but also caused the decomposition of the polymer. A solution to this was to scan multiple times the same area with a lower laser power that did not cause decomposition. At this stage, single layers of laser sintered PFA were fabricated and found to be porous, flexible, with a fabric feeling to the touch, and with potential membrane applications. THV was used in material jetting in different solvents and concentrations with two manufacturing systems: Dimatix and PICO Pµlse. The Dimatix was able to print very diluted formulations (1 wt%) and generate very thin uniform coatings and patterns down to 5-10 nm in thickness. The PICO Pµlse was able to print more concentrated formulation (10-20 wt%) into thicker films with higher throughput but lower resolution. The combination of the two printers could allow for both high throughput and resolution. The samples showed the potential to be used in the slow release of drugs. Overall, this PhD showed that fluoropolymers have the potential to be used in AM in several applications and that they would benefit from high temperature systems and the collaboration of the powder suppliers to design polymer grades with properties tailored for AM (particle size, viscosity, etc.).